Analisis Faktor-Faktor Yang Mempengaruhi Kepuasan Pelanggan Café Kopigo Bukittinggi - Zulmadian, Siska; Widianita, Rika (Portofolio: Jurnal Ekonomi, Bisnis, Manajemen, dan Akuntansi, 2025)
This research focuses on analyzing process factors that influence customer satisfaction at Café Kopigo Bukittinggi. This research is motivated by the importance of customer satisfaction in maintaining competitiveness in the culinary industry. This research utilizes a quantitative approach as a method with factor analysis techniques, information techniques collected through interviews and questionnaires with 99 respondents selected using a random sampling method. The results of the analysis show that of the 32 variables studied, there are eight factors that contribute to customer satisfaction. Among these factors, the most dominant are price, emotional service quality, product quality, employee appearance and performance, cleanliness and price competition, product consistency and customer comfort. Therefore, to increase customer satisfaction, Café Kopigo Bukittinggi needs to focus on improving service quality and adjusting prices, as well as creating a more pleasant atmosphere for customers.